Kontribusi Wanita dalam Keberlangsungan Agribisnis Perspektif Ekonomi Syariah - Rosida, Ika Nazilatur (Journal of Industrial and Syariah Economics, 2024)
This research aims to analyze women's contribution to agribusiness sustainability from a Sharia economic perspective. Human resources are an important asset in the sustainability of agribusiness. The sustainability of agribusiness is one of the efforts to fulfill the needs of the people. This research is descriptive qualitative research with a library research approach. Data collection in this research was by library, reading, and taking notes. The data collected in this research came from online books, journals, scientific articles, and literature reviews containing the Contribution of Women in the Sustainability of Agribusiness from a Sharia Economic Perspective. The research results show that there has been an increase in the number of female workers in the formal and informal sectors. This also shows that women contribute to the sustainability of agribusiness in an effort to improve the welfare of the people and achieve a balanced economy in accordance with sharia economic principles. The principles of Sharia economics include several principles of monotheism, justice, benefit, mutual help, and balance.